2003
DOI: 10.1023/b:jcam.0000021831.47952.a7
|View full text |Cite
|
Sign up to set email alerts
|

A structure-activity relationship study of catechol-O-methyltransferase inhibitors combining molecular docking and 3D QSAR methods

Abstract: A panel of 92 catechol-O-methyltransferase (COMT) inhibitors was used to examine the molecular interactions affecting their biological activity. COMT inhibitors are used as therapeutic agents in the treatment of Parkinson's disease, but there are limitations in the currently marketed compounds due to adverse side effects. This study combined molecular docking methods with three-dimensional structure-activity relationships (3D QSAR) to analyse possible interactions between COMT and its inhibitors, and to incite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 24 publications
3
24
0
Order By: Relevance
“…Both approaches resulted in equivalent statistical significance for every test and thus only the results of the LOO analyses are detailed below. Inhibitors of angiotensin converting enzyme 114 ACHE [11] Inhibitors of acetyl-cholinesterase 111 AI [25,29] Steroid aromatase inhibitors 78 ARB [30] Nonpeptide angiotensin II receptor antagonists 28 ATA [31] Anti-tuberculosis agents 94 BZR [11] Inhibitors of benzodiazepine receptor 163 CBRA [32] Cannabinoid CB1 receptor agonists 32 COMT [33] Inhibitors of catechol-O-methyltransferase 92 COX2 [11] Inhibitors of cyclooxygenase-2 322 DAT [34] Piperidine analogues for dopamine transporter 42 DHFR [11] Inhibitors of rat dihydrofolate reductase 397 DR [35,36] Antagonists of dopamine receptor 38 ECR [37] Binding of diacylhydrazine to ecdysone receptor 50 EDC [38] Estrogen disrupting chemicals 123 GHS [39] Growth hormone secretagogue mimics 31 GPB [11] Inhibitors of glycogen phosporylase b 66 GSK3B [40] Inhibition of Glycogen synthase kinase 3 42 HIVPR [41] Inhibitors of human immunodeficiency virus protease 113 HIVRT [42,43] Inhibition of HIV-1 reverse transcriptase 101 KOA [44] Kappa opioid antagonists 39 MX [45] Mutagenicity of mutagen X analogues 29 PDE [46] Inhibition of phosphodiesterase-IV 29 PTC [47] Phase-transfer asymmetric catalysts 40 RYR [25,48] Binding of ryanoids to the ryanodine receptor 18 STEROIDS [3,25] Binding of steroids to carrier proteins 21 TCHK [49] Inhibition of trypanosoma cruzi hexokinase 42 THERM [11] Inhibitors of thermolysin 76 THR [11] Inhibitors of thrombin 88 TP2A [50] Inhibition of topoisomerase-IIa 25 YOPH [51] Inhibitors of yersinia protein tyros...…”
Section: Resultsmentioning
confidence: 99%
“…Both approaches resulted in equivalent statistical significance for every test and thus only the results of the LOO analyses are detailed below. Inhibitors of angiotensin converting enzyme 114 ACHE [11] Inhibitors of acetyl-cholinesterase 111 AI [25,29] Steroid aromatase inhibitors 78 ARB [30] Nonpeptide angiotensin II receptor antagonists 28 ATA [31] Anti-tuberculosis agents 94 BZR [11] Inhibitors of benzodiazepine receptor 163 CBRA [32] Cannabinoid CB1 receptor agonists 32 COMT [33] Inhibitors of catechol-O-methyltransferase 92 COX2 [11] Inhibitors of cyclooxygenase-2 322 DAT [34] Piperidine analogues for dopamine transporter 42 DHFR [11] Inhibitors of rat dihydrofolate reductase 397 DR [35,36] Antagonists of dopamine receptor 38 ECR [37] Binding of diacylhydrazine to ecdysone receptor 50 EDC [38] Estrogen disrupting chemicals 123 GHS [39] Growth hormone secretagogue mimics 31 GPB [11] Inhibitors of glycogen phosporylase b 66 GSK3B [40] Inhibition of Glycogen synthase kinase 3 42 HIVPR [41] Inhibitors of human immunodeficiency virus protease 113 HIVRT [42,43] Inhibition of HIV-1 reverse transcriptase 101 KOA [44] Kappa opioid antagonists 39 MX [45] Mutagenicity of mutagen X analogues 29 PDE [46] Inhibition of phosphodiesterase-IV 29 PTC [47] Phase-transfer asymmetric catalysts 40 RYR [25,48] Binding of ryanoids to the ryanodine receptor 18 STEROIDS [3,25] Binding of steroids to carrier proteins 21 TCHK [49] Inhibition of trypanosoma cruzi hexokinase 42 THERM [11] Inhibitors of thermolysin 76 THR [11] Inhibitors of thrombin 88 TP2A [50] Inhibition of topoisomerase-IIa 25 YOPH [51] Inhibitors of yersinia protein tyros...…”
Section: Resultsmentioning
confidence: 99%
“…We have shown previously that 3D-QSAR methods are useful approaches if one wishes to evaluate the structural features that are important for inhibition potency against CYP enzymes and other targets. 23,27,28,31,32 In this study, we showed that novel CYP2A6 inhibitor structures can be designed using CoMFA based on homology modelling. As CYP2A6 crystal structures became available during this work, we were able to ascertain the accuracy of the CoMFA model using the crystal structure data.…”
Section: Discussionmentioning
confidence: 96%
“…Also the leavehalf-out (LHO) method has been reported to give a good estimation of the model predictivity. 27,28 The CoMSIA model yielded slightly lower statistical values than the CoMFA model.…”
Section: Statistics Of Comfa and Comsia Modelsmentioning
confidence: 87%
“…This has mostly, however, been simulations using the QM-MM method (Quantum Mechanics-Molecular Mechanics) to focus on the details of the catalytic reaction itself [10][11][12][13][14][15] or QSAR-type analysis [16]. In addition to the interest in the activity and …”
Section: Introductionmentioning
confidence: 99%